Success Factors of Government Digital Applications in Public Service Delivery: A Systematic Literature Review - Rifqi Fahrudin; Zainal Arifin Hasibuan; Bobby Kurniawan; Sri Supatmi (Software Engineering in Computing Systems, 2026)
The rapid development of digital government applications has significantly transformed public service delivery; however, their success remains inconsistent due to the complexity of multiple influencing factors. Many government digital systems experience low adoption, usability challenges, and limited impact on service quality, indicating the need for a comprehensive understanding of the determinants of success. This study aims to identify and synthesize the critical success factors of government digital applications in public service delivery. To achieve this objective, a systematic literature review (SLR) was conducted using the Scopus database, applying a predefined search strategy and PRISMA-based screening process. From an initial set of 176 articles, 44 relevant studies were selected and analyzed using a coding framework to classify success factors into four dimensions: technological, organizational, user, and governance. The results show that digital government success is inherently multidimensional, with user-related factors such as trust, usability, and satisfaction emerging as the most dominant, while technological factors function as enabling components and organizational and governance factors ensure sustainability and effectiveness. Furthermore, the findings reveal significant research gaps, particularly the lack of integrated frameworks and the fragmented treatment of success factors in existing studies. This study concludes by proposing an integrated classification framework that provides a comprehensive understanding of digital government success and offers practical guidance for policymakers in designing more effective and sustainable digital public services.